Impaired CD4+ cell recovery during antiretroviral therapy in patients with HIV resistance mutations - Sühs, Kurt-Wolfram; Diem, Ricarda (Archives of virology, 2012)
Antiretroviral therapy is limited by the development of human immunodeficiency virus (HIV) resistance mutations. Although resistance testing is recommended during therapy failure, little is known about the optimal time points for testing or its impact on treatment. In this study, we investigated HIV polymorphisms and mutations and assessed their influence on the outcome of highly active antiretroviral therapy (HAART). We focused on viral load and CD4+ cell counts as the most important parameters for therapy response. Resistance mutations were present in 19% of all patients prior to antiretroviral treatment. Mutations causing direct antiretroviral drug resistance were observed in 10%. Analyzing therapy response, we found a significant correlation between resistance mutations and impaired CD4+ cell recovery six months after the initiation of antiretroviral treatment. Lower CD4+ cell counts were also observed in a subgroup of patients infected with a virus presenting mutations that directly lowered drug susceptibility.